AFFECT OF JOB SATISFACTION, WORK STRESS, AND WORK ENVIRONMENT ON POTENTIAL TURNOVER INTENTION OF OPERATOR LEVEL EMPLOYEES AT PT. PRIMA SEJATI SEJAHTERA 3 - Fidyah Yuli Ernawati; Arini Novandalina; Usman Abdul Majid (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The purpose of this study is to determine job satisfaction, work stress, and work environment on turnover intention at PT. Prima Sejati Sejahtera 3 to the operator level employees. High employee turnover rates result in organizations are becoming ineffective, losing experienced employees and needing to train new employees. High job satisfaction and a good work environment will affect the decrease in turnover intention, while high work stress will affect the increase in turnover intention. The variables used in this study include the independent variables of job satisfaction, work stress and work environment, while the dependent variable is turnover intention. The population in this study was the employees of PT. Prima Sejati Sejahtera 3. The number of samples used in the study was 60 employees, using the Slovin method. Methods of data collection were using the method of observation and questionnaires. Data analysis used multiple linear regression analysis with the help of SPSS program. Based on the research results, it is known that the multiple linear regression equation Y = 16,328 – 0.496 +0.303 – 0.258. The results of data analysis carried out on the indicators used in this study are all valid and reliable. As the matter of fact for the classical assumption test, the overall data is normally distributed. The results of the t test show that the job satisfaction variable has a negative effect with a significant value of 0.005, the work stress variable has a positive effect with a significant value of 0.021 and the work environment variable has a negative effect with a significant value of 0.148. F test results show that all variables have a simultaneous effect or together with a significant value of 0.016. The result of the coefficient of determination test is 40.9%. This study concludes that there is a significant negative effect on job satisfaction and there is a significant positive effect of work stress and the work environment and an insignificant negative effect on employee turnover intention at PT. Prima Sejati Sejahtera 3. Suggestions for companies should provide additional incentives for employees, placing employees according to their expertise, add cleaning staff. For other researchers can add other objects and variables. Keywords: Job Satisfaction, Job Stress, Work Environment, Turnover Intention